Acrylamide Versus Agarose Efficiency to recover Trace DNA (without PCR) on 70% Ethylated Swab Versus Distilled Water Swab from Spectacles - Simon Martin Manyanza Nzilibili (Punjab Academy of forensic Medicine & Toxicology, 2019)
Introduction Swabbing method is one of the established methods in recovering forensic traces. The used swab is suggested to be effective while in a moist state. Different fluids have been proposed then with minimal highlight to ethylated swabbing (prepared from ethanol) which is also found usable and friendly during extraction and storage of sample among other efficacy. Material and Methods This study analyzes the significant use of 70% ethylated swab run simultaneously with distilled water swab to potentiate the findings under 6% acrylamide and 2% agarose electrophoresis without PCR. Besides assessing the use of these swabs (70% ethyl and distilled water) and its electrophoretic reaction on the two gel, this study also studied the usefulness on spectacle as a potential source of traces. Results 70% ethylated swab is found to concentrate DNA sample (1421μg/ml) two times more compared to distilled water swab (654.5μg/ml). In terms of purity of recovered DNA, 70% ethylated swab presented nearly similar measurement to distilled water swab (1.219 to 1.176 purity ratio respectively). Agarose electrophoresis was not able to detect DNA molecule hence the absence of visualized DNA fragments as band contrast from both swabs. On acrylamide gel electrophoresis, DNA molecule migration displayed multiple bands contrast with 70% ethylated swab; deep and concentrated towards positive electrode while lighter bands lagged near the negative end. Distilled water swab contrasted one deep band near the negative terminal electrode. Conclusion 6% acrylamide gel electrophoresis in absence of PCR is effective to profile trace DNA compared to agarose. In addition, 70% ethylated swab is a useful method in recovering trace DNA to successful DNA analysis. Also, the spectacle is a potential evidence for trace DNA either found at the crime scene for criminal linkage or purposed forensic investigation.